2016
DOI: 10.1016/j.biocontrol.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Augmentative releases of Diachasmimorpha longicaudata (Hymenoptera: Braconidae) for Ceratitis capitata (Diptera: Tephritidae) control in a fruit-growing region of Argentina

Abstract: Field-open augmentative releases were conducted to assess the efficacy of Diachasmimorpha longicaudata (Ashmead) for the regulation of Ceratitis capitata (Weidemann) infesting Ficus carica (L.) in a commercial area located in a fruitproducing irrigated-valley of San Juan, central-western Argentina. Parasitoids were reared on Sensitive Lethal TemperatureVienna-8 strain of C. capitata at the BioPlanta San Juan facilities, and were weekly released throughout 9 weeks over two experimental plots of ca. 2.3 hectares… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 29 publications
3
18
1
Order By: Relevance
“…The ability to fly has also been used as a parameter to measure the ability of the parasitoid to reach its host (Cancino et al, 2006a). In this study, no differences were found between treatments for the variables like sex ratio and fertility, but for parasitism there were differences, the highest percentages of parasitism were those found in 60 cc and 70 cc treatments (65%, Table 1), these percentages were comparable with those obtained by Sánchez et al (2016) in the field, which were also between 16% and 75% on Ceratitis capitata. It is important to note that the fertility variable showed significant differences between days (Fig 1).…”
Section: Resultssupporting
confidence: 59%
“…The ability to fly has also been used as a parameter to measure the ability of the parasitoid to reach its host (Cancino et al, 2006a). In this study, no differences were found between treatments for the variables like sex ratio and fertility, but for parasitism there were differences, the highest percentages of parasitism were those found in 60 cc and 70 cc treatments (65%, Table 1), these percentages were comparable with those obtained by Sánchez et al (2016) in the field, which were also between 16% and 75% on Ceratitis capitata. It is important to note that the fertility variable showed significant differences between days (Fig 1).…”
Section: Resultssupporting
confidence: 59%
“…Host location and host acceptance behavior has been widely studied in the generalist fruit fly parasitoid Diachasmimorpha longicaudata (Ashmead) (Greany et al 1977, Lawrence 1981, Carrasco et al 2005. This species is exotic in the Americas where it has been successfully reared for augmentative biological control of Anastrepha (Schiner) fruit flies in Mexico (Montoya et al 2000(Montoya et al , 2007 and in Florida USA (Sivinski et al 1996); and for Ceratitis capitata (Wiedemann) in Argentina (Sanchez et al 2016). However, there is a guild of native opiine braconid parasitoids (Sivinski et al , 2001 with potential as biocontrol agents, for which little information exists regarding their foraging and host acceptance behavior.…”
Section: Introductionmentioning
confidence: 99%
“…To sum up, findings from this study add knowledge on chemically mediated foraging behaviours of D. longicaudata and A. pelleranoi , and highlight the potential use of both parasitoids species for augmentative release programs in Argentinean fruit‐growing regions where A. fraterculus and C. capitata coexist. In Argentina, D. longicaudata is mass reared on larvae of C. capitata and mass released against this pest (Sánchez et al., ). However, in several Argentinean regions, the presence of A. fraterculus is also a main concern for growers.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, D. longicaudata is being mass reared on larvae of a Ceratitis capitata temperature‐sensitive lethal (tsl) vienna‐8 genetic sexing strain at the Bioplanta San Juan facility, Argentina (Suárez et al., ), and is being mass released against Medfly in fruit‐producing irrigated‐valleys of San Juan, central‐western Argentina (Sánchez et al., ). Regarding A. pelleranoi , it has been laboratory‐reared on both C. capitata and Anastrepha fraterculus (Gonçalves et al., ; Núñez‐Campero, Aluja, Rull, & Ovruski, ), and it is a candidate species to be incorporated in augmentative biological control (Aluja, Ovruski, Guillén, Oroño, & Sivinski, ).…”
Section: Introductionmentioning
confidence: 99%